An Assessment of Water, Sanitation and Hygiene Access in Bangladesh's Community Health Clinics - Joseph, George (World Bank, Washington, DC, 2019)
Adequate water, sanitation and hygiene (WASH) in health care facilities plays a critical role in ensuring improved health care utilization and reducing disease burden due to reinfection. WASH in health facilities is now gaining momentum with the new SDG targets that governments have vowed to meet. This goal calls for a baseline examination of existing WASH conditions in health facilities. Using data collected through a census of all community health clinics in Bangladesh, this paper presents an analysis of the state of WASH in Bangladesh's rural, public health facilities highlighting that the lack of functionality of WASH facilities is a widespread problem across the country. The paper also identifies priority areas for action when considering the prevalence of poverty and chronic undernutrition at the upazilla level.